Expanding the knowledge of Helicobacter pylori – new directions, new challenges - Wronecki, Jakub; Tywanek, Ewa; Trojanowska, Paulina; Skrzydło-Radomańska, Barbara; Zwolak, Agnieszka; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2020)
Introduction Helicobacter pylori (H. pylori) infection is prevalent worldwide. As it is a known carcinogen, causing multitude of gastrointestinal end extra-gastric disorders, the eradication therapy is now indicated for every patient diagnosed with this infection. This approach may prove however to be improper, since it is now known, that not every strain of this species is pathogenic, therapy may be unsuccessful and drug resistance is ever increasing problem. A brief description of the state of knowledge: H. pylori is a species representing multiple strains with distinct regional genetic markup. Its prevalence is high in the general population, but in the recent years there have been reports of decreased presence in the developed countries. This paper reviews most important known genetic diversity markers and their impact on virulence and toxicity of species. It also covers possible new ways to combat the infection. Conclusion With increased possibility of genetic sequencing, there may be possibility for custom-tailored eradication therapy of H. pylori in the future.